Factors Influencing Competitiveness of Small and Medium Enterprises (SMEs) in Nairobi County, Kenya - Irungu, Anne; Arasa, Robert (My University, 2017)
The purpose of this study was to examine factors influencing firm competitiveness among the Small and Medium Enterprises in Nairobi, Kenya. Specifically the study set out to examine the influence of strategic leadership, technology, resources and organization culture on competitiveness of Small and Medium Enterprises in Nairobi. The study adopted a descriptive research design. The study population comprised of SMEs in Nairobi which fall within the top 100 SMEs in Kenya. There are 79 SMEs from Nairobi County in the Top 100 SMEs in Kenya. A sample size of 25 SMEs which represented 30% of the target population was selected through stratified random sampling. The stratification was based on five business sector categories (real estate, supplies, services, distribution and manufacturing). The study utilized primary data which was collected from top management employees through the use of questionnaire. Data was analyzed using both descriptive and inferential statistics. Correlation analysis was employed to aid in establishing the nature and strength of the relationships between variables of interest. Correlation analysis results indicate that strategic leadership, adoption of relevant technology, resources availability and organization culture has a positive and significant relationship with firm competitiveness. The study concludes that sustainable competitive advantage of the firm stems from effective strategic leadership, adoption of technology, resources availability and effective organization culture. The study recommends that SMEs should embrace various competitive strategies to remain relevant in the market and achieve the required competitiveness. The SMEs managers should embrace strategic leadership practices, benchmark on best practices to ensure constant touch with their customers, embrace adoption of appropriate technology towards realizing higher levels of efficiency and effectiveness, ensure optimal utilization of resources, and cultivate a good balance between the organization culture and the organization processes so as to enhance competitive advantage. This study was confined to factors influencing organizational competitiveness of small and medium enterprises within Nairobi County. Other studies could be pursued in terms of expanding the geographical setting and taking recognition of other variables that could intervene and or moderate the investigated relationship.
Keywords: Competitiveness; SMEs; Leadership; Technology; Resources; Culture